Working with troubled youth in schools : a guide for all school staff - McAuliffe, Garrett (Bergin & Garvey, 2002)
This work presents a practical guide to creating effective, school-based responses to the difficult problem of dealing with troubled youth in schools, based on an "ecological" approach to collaboration among school professionals and community members. The two themes of "prevention" and "connection" pervade the practices that are described